Problem-Solving Proficiency Profile in Problem-Based Learning Model for Eighth-Grade Students on the Subject of Pressure in Matter - Ningtyas, Winarti Eka Wahyu; Yunus, Muhammad; Komariyah, Laili (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2023)
The Problem Based Learning (PBL) model is considered as one of the effective approaches to develop problem-solving skills in students. Hence, the purpose of this study is to assess the problem-solving abilities of eighth-grade students in SMPN 3 Samarinda using the PBL model. The research design employed in this study is descriptive quantitative. The data collection took place at SMPN 3 Samarinda with a total sample of 26 class VIII students. This research yielded the finding that the ability to solve problems for the indicator of understanding the problem reaches 73.50%, then the indicator of making plans obtains the proportion of 49.15%, then the indicator of carrying out the plan 40.17% and finally the indicator of re-examination is obtained 37.18%. So that the average proportion of all indicators capable of solving problems is 50%, this proportion is included in the sufficient category. In accordance with these findings, it can be interpreted that more science material is needed which is taught using the PBL model so that the profile of the problem-solving skills of the students can be better